Analisis Tingkat Kesehatan Koperasi Simpan Pinjam Torganda II Rantelemo Kabupaten Tana Toraja - Ardianty, Wilma Dian; Sape, Barnice; Matasik, Ade Lisa; Ramba, Dina (Jurnal Ekonomi, Bisnis dan Terapan (JESIT), 2022)
This study aims to determine the health level of bad loans at the Torganda II Rantelemo Savings and Loans Cooperative, Tana Toraja Regency 2019-2021. The benefit of this research is that it can contribute ideas, information for the leadership of KSP Torganda II Rantelemo in making decisions when providing loans to members who apply for loans and increase knowledge or insight in analyzing credit in cooperatives. The type of research used is descriptive quantitative, namely by recording and analyzing data obtained from the Torganda II Rantelemo Savings and Loans Cooperative, Tana Toraja Regency. Analysis of the data used to analyze the soundness level of bad loans in KSP II, namely the ratio of Non-Performing Loans (NPL). Based on the results of the study, it showed that the level of bad loans at KSP Torganda II was determined to be unhealthy because it exceeded the standards set by the Cooperative Service through the Minister Of Cooperatives And Small And Medium Enterprises.